Effects Of High Body Mass Index On Fetomaternal Outcome - Bushra Noor Khuhro; Rubina Hussain (ziauddin University, 2024)
ABSTRACT Background: In our country increasing prevalence of obesity among fertile women is growing public health concern, womenwith BMI more than 30 are at greater risk adverse reproductive health outcome,this study will provide over view of complications related to high BMI. Objective: To identify the effects of high body mass index (BMI) on feto-maternal outcome Material and Methods: 100 patients were selected randomly from OPD who matchedinclusion criteria, their BMI checked at booking and at term, Study design was Case series conducted at Ziauddin University and hospitals Karachi, in 9 month of time duration. Then patients were followed for any complications Results: in our study, results showed PIH developed to 38% of patients, gestational diabetes mellitus to 15%, preeclampsia to 15%, PPH to 13%, Threatened miscarriage occurred to 5 %, woundinfection developed to 5%, and 37% babies admitted to NCU of patients who followed for complication with high BMI. According to calculations 55% patients with high BMI delivered spontaneously,28% ended up in emergency LSCS, 11% were elective LSCS and 1 delivered by instrumentaldelivery . Conclusion: High BMI has adverse effect on PIH,GDM, pre eclampsia, mode of delivery, and threatened miscarriage, whereas, there is no effect of high BMI on woundinfection, elective LSCS, instrumental delivery and congenital anomaly which maybe due to other factors . More work is required. Key Words: BMI, PIH, GDM, WoundInfection.